Asymptomatic rheumatoid meningitis revealed by magnetic resonance imaging, followed by systemic rheumatic vasculitis: A case report and a review of the literature. Issue 2 (4th March 2019) - Matsuda, Shogo; Yoshida, Shuzo; Takeuchi, Tohru; Fujiki, Yohei; Yoshikawa, Ayaka; Makino, Shigeki
Abstract: We report the case of a 66-year-old man with seropositive rheumatoid arthritis who developed neurologically asymptomatic rheumatoid meningitis (RM) revealed by MRI. RM worsened and chest CT showed pericardial effusion, pleural effusion, and bilateral consolidation, and his serum C3 level was decreased. We diagnosed systemic rheumatic vasculitis based on these findings. After a review of more than 20 previously reported cases of RM, this is the first case of RM without central nerve system symptoms.